Alice in wonderland - Robson; Kristeen (London Mind to Mind, 2010)
The story follows Alice, a curious girl who falls down a rabbit hole into the fantastical world of Wonderland. There, she encounters a series of eccentric characters, including the White Rabbit, the Cheshire Cat, and the Mad Hatter. As Alice navigates through this peculiar land, she experiences a series of bizarre and humorous adventures. The book captures the essence of Lewis Carroll$1 (Bs classic tale, emphasizing imagination, curiosity, and the joy of exploration.s